Home‐field advantages of litter decomposition increase with increasing N deposition rates: a litter and soil perspective. (10th April 2017) - Li, Ying‐Bin; Li, Qi; Yang, Jun‐Jie; Lü, Xiao‐Tao; Liang, Wen‐Ju; Han, Xing‐Guo; Martijn Bezemer, T.
Summary: Differences in litter quality and in soil microbial community composition can influence the litter decomposition and 'home‐field advantage' (HFA). However, our knowledge about the relative role of litter and soil characteristics on litter decomposition and HFA effects is still limited, especially under long‐term N deposition. We collected soil and two types of litter (monospecific and mixed species litter) from five replicate plots from a long‐term N deposition field experiment with seven N addition treatments (0, 2, 5, 10, 15, 20, 50 g N m −2 year −1 ). We examined the effects of N addition on litter quality and soil characteristics. We then carried out a three‐pronged microcosm decomposition experiment with (i) litter from different N addition treatments decomposed on a standard field soil; (ii) standard litter decomposed on soils from the different N addition treatments; and (iii) litter decomposed on soil from the same N addition treatment plot. Decomposition of litter on standard soil was influenced strongly by the N addition treatment, but did not consistently decrease or increase with increasing N addition rates. Instead, decomposition of standard litter on soils collected from different N addition treatments decreased with increasing rates of N addition. Decomposition of litter on soil collected from the same plot increased with increasing N addition rates. Soil characteristics explained more of the variation in litter decomposition than litter characteristics. There was a clear HFA effect for litter decomposition, both from a litter and from a soil perspective. HFA effects increased when the dissimilarity in litter quality (N content and C : N ratio) increase among the different N addition treatments and the soil effect was strongest at high N addition rates. N addition influenced litter decomposition by changing both litter and soil characteristics. Importantly, N addition decreased the capability of soils to decompose litter and it increased the HFA effect indicating that soils decomposed local litter better than other litter, due to specialization in soil communities. Nitrogen deposition is an important threat to ecosystems worldwide and our study emphasizes that ecosystem functions such as decomposition can be greatly influenced by these global changes. A lay summary is available for this article. Abstract : Lay Summary